2010
DOI: 10.3892/etm.2010.171
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of integrins αvβ3, αvβ5 and α5β1, and their ligands, fibrinogen, fibronectin, osteopontin and vitronectin, in frozen sections of human oral head and neck squamous cell carcinomas

Abstract: Abstract. integrins mediate the interaction of cells with the extracellular matrix and are believed to be involved in tumor cell survival and metastasis, and in tumor angiogenesis. We used immunohistochemistry of fresh-frozen human tumor tissues to analyze the presence of integrins αvβ3, αvβ5 and α5β1, which are believed to be involved in tumor growth and migration, together with integrin ligands, vitronectin, osteopontin, fibronectin and fibrinogen, in human oral squamous cell carcinomas. Samples of squamous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 64 publications
(44 reference statements)
2
45
0
Order By: Relevance
“…FN (secreted or assembled) was undetectable in a set of HNSCC lines (Fig. 1e), consistent with the observed restriction of FN expression to stromal cells in the majority of these tumours, and in line with previous reports19.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…FN (secreted or assembled) was undetectable in a set of HNSCC lines (Fig. 1e), consistent with the observed restriction of FN expression to stromal cells in the majority of these tumours, and in line with previous reports19.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Fig. 5a, αvβ3 integrin is not expressed by these cells, consistent with its expression in the endothelial rather than epithelial cells of these tumours19. Moreover, the use of αvβ5 blocking antibody had no impact on collective migration speed or directionality (Fig.…”
Section: Resultssupporting
confidence: 79%
“…One of the most important targets of fluorescent probes in oncology is avß3 integrin, which shows large expression in neovessels and certain tumors, including HNSCC [1][2][3]. It plays an important role in angiogenesis, cell proliferation and migration and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It requires fluorescent probes that specifically target cancer cells. One of the most important targets is ˛vß3 integrin, which is widely expressed on the surface of tumor-vessel endothelial cells and by most tumor cells, including HNSCC, during migration or by cells located on invasion frontlines [1][2][3]. Previous studies showed that near-infrared fluorescence imaging targeting ␣vß3 integrin provides benefit in HNSCC surgery by improving resection quality through the detection of tumor residue within the surgical bed that would be invisible to the naked eye even under magnifying lenses, so that the residue would be overlooked in purely macroscopically guided resection.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Though diagnostic techniques have improved over the ages, yet the survival rates remain to be poor and have been the same in the last few years, with a 5-year survival rate of only 50% cases in oral squamous cell carcinoma (OSCC) from the time of diagnosis. [2] The disease shall progress at its own pace and continue to pose as a threat. So, we need to think beyond our present domains and make efforts in the regard.…”
Section: Introductionmentioning
confidence: 99%